2019
DOI: 10.1029/2019sw002159
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Multiple Data Types to a Regional Ionosphere Model With a 3D‐Var Algorithm (IDA4D)

Abstract: For the purpose of building a regional (bound 20–60°N in latitude and 110–160°E in longitude) ionospheric nowcast model, we investigated the performance of IDA4D (Ionospheric Data Assimilation Four‐Dimension) technique considering International Reference Ionosphere model as the background. The data utilized in assimilation were slant total electron content (STEC) from 27 ground GPS (Global Positioning System) receiver stations and NmF2 (ionospheric F2 peak density) from five ionosondes and COSMIC (Constellatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 54 publications
0
32
1
Order By: Relevance
“…These grid resolutions resulted in 24 and 16 latitudinal and longitudinal bins, respectively. Several studies (e.g., Krankowski et al, 2011 andMengist et al, 2019) that have used COS-MIC data commonly consider measurements with horizontal smear > 1500 km prone to errors, and they reject such measurements. We established that after applying this restriction, there were ∼ 40 RO measurements per day during the year 2013 over our study area (not shown here).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These grid resolutions resulted in 24 and 16 latitudinal and longitudinal bins, respectively. Several studies (e.g., Krankowski et al, 2011 andMengist et al, 2019) that have used COS-MIC data commonly consider measurements with horizontal smear > 1500 km prone to errors, and they reject such measurements. We established that after applying this restriction, there were ∼ 40 RO measurements per day during the year 2013 over our study area (not shown here).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…As one of the IGS analysis centers, Center for Orbit Determination in Europe (CODE) provides Global Ionosphere Maps (GIMs) containing vertical TEC data daily using the GNSS data collected from over 200 tracking stations of IGS and other institutions. Several studies have used GIMs from CODE and other IGS analysis centers such as the Jet Propulsion Laboratory (JPL) to construct TEC models (Jakowski et al, 2011a;Mukhtarov et al, 2013;Ercha et al, 2012;Sun et al, 2017). Jakowski et al (2011a) proposed the Global Neustrelitz TEC Model (NTCM-GL) that describes the average TEC under quiet geomagnetic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 3DVAR does not involve the time evolution of the state within a given time window (e.g., 15 min) and assumes all measurements have the same time‐stamp weighting. This is very similar to the second task (i.e., Update) of Kalman filters and thus is normally used in data assimilation based on empirical ionospheric models where the forward prediction is not directly available (although sometimes this can be implemented by using a Gauss‐Markov filter method; e.g., Aa et al., 2016; Bust et al., 2004, 2007; Mengist et al., 2019). In contrast, 4DVAR takes into account the time‐dependent weighting of different terms in the cost function within a given window, which makes the estimation of the error covariance an even more challenging and time‐costing issue (Ssessanga et al., 2019; C. Wang et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These include: Appropriate estimation of the background error covariance: A major difficulty in developing an accurate and reliable assimilation system lies in a proper description of the background error covariance, which is a key factor that determines the weighting contribution and the spread of information. Many data assimilation efforts, especially variation‐based algorithms, often use time‐invariant static background error covariance, based on certain assumptions of unbiased Gaussian distribution of ionospheric correlation length as deduced from climatological statistics (e.g., Aa et al., 2016; Bust et al., 2004, 2007; Mengist et al., 2019; Ssessanga et al., 2019; C. Wang et al., 2004; Yue et al., 2007). In reality, however, the ionospheric spatial correlation length and associated background error covariance may not be optimally represented under these assumptions, especially when the ionosphere exhibits considerable disturbances during space weather events.…”
Section: Introductionmentioning
confidence: 99%